Expression of Cyclooxygenase-2, p53 and Ki-67 in Gastric Cancer - Joo, Young-Eun (The Korean Academy of Medical Sciences, 2006)
It has been reported that p53 mutation may contribute to upregulate cyclooxygenase (COX)-2 expression that is observed in malignant tissues. These molecules are involved in carcinogenesis by affecting tumor cell proliferation. The aim of this study was to examine the relationship between COX-2 or p53 expression and clinico-pathological characteristics including tumor cell proliferation in gastric cancer. COX-2 and p53 expressions were investigated with immunostaining, in tissue specimens obtained from 119 patients who underwent surgery for gastric cancer. The Ki-67 labeling index (LI) was counted by Ki-67 immunostaining. COX-2 and p53 expressions correlated significantly with depth of tumor invasion. However, there was no association between COX-2 or p53 expression and survival. p53 expression did not correlate with COX-2 expression. There was no significant difference in various clinicopathological variables between Ki-67 LI subgroups. The mean Ki-67 LI value of COX-2 positive tumors was significantly higher than that of negative tumors. The mean Ki-67 LI value of p53 positive tumors was not significantly higher than that of negative tumors. The mean Ki-67 LI value of both COX-2 and p53 positive tumors was significantly higher than that of both negative tumors. These results imply that COX-2 expression is associated with tumor cell proliferation of gastric cancer.